Ethiopian Churches Commemorating Military Victories of the Solomonic Kingdom over the Betä Ǝsraʾel (Ethiopian Jews) - Kribus, Bar (Religions, 2025)
During the Middle Ages and Early Modern Period, most Jews lived as a minority under Christian or Islamic rule. By contrast, the Ethiopian Jews, the Betä Ǝsraʾel, maintained political autonomy in parts of Ethiopia until the seventeenth century. From the fourteenth century, they were engaged in a series of wars against the Christian Solomonic Kingdom. Following Christian military victories over the Betä Ǝsraʾel, the victors erected churches in the newly conquered lands. Some were built on the sites of battles and over Betä Ǝsraʾel strongholds to commemorate the Solomonic victory. While churches dedicated to historical events are common, those memorializing Christian military victories over Jews are largely without parallel elsewhere. This article provides an overview of what is known about their location, characteristics, and symbolism, and discusses their contribution to understanding the Betä Ǝsraʾel polity.